Human hair keratin gradient hydrogels for skin regeneration - Yee, Marin Zhen Lin (2022)
Gradient hydrogels have received attention due to the possibility to incorporate physical and chemical gradients to mimic those present in vivo with higher relevance. Human hair keratins (HHK) are an established biomaterial in forming various templates for biomedical applications essentially due to the presence of versatile functional groups and the cell adhesion motif LDV (leucine-aspartic-valine). By exploiting the high cysteine content in HHK and their affinity to silver ions, we have developed a novel gradient HHK hydrogel through a single-step fabrication process. The gradient gelation is facilitated by the diffusion of silver ions into solubilized HHK through a thin membrane first formed upon a dropwise addition of HHK into the ion bath. This gradient was confirmed through Turbiscan analysis where transmission decreased as light travelled across the hydrogel. Also, rheological studies highlighted a gradient breakdown of the hydrogel where the storage modulus remained greater than the loss modulus at high strain despite an initial decrease. This gradient profile rendered the hydrogel with improved toughness. Moreover, scanning electron microscopy unveiled the presence of a dual microstructure within a single construct: a porous spongy layer and a non-porous compact layer, which mimics the dermis and epidermis of native skin, respectively. Unconstrained by silver, a HHK gradient hydrogel could also be formed with other biologically relevant metal ions. Alongside HHK, gelatin methacryloyl was found suitable to form a composite gradient hydrogel, displaying potential for skin regeneration. Beyond the skin, this tunable HHK gradient hydrogel system is potentially tailorable towards other biomedical applications.